Music in Motion - Sæther, Eva; Hemetek, Ursula; Clausen, Bernd (2009)
Diverse musical cultures of migrant and minority communities have existed in Europe for centuries and shaped its countries significantly. As part of an EU-funded project this volume deals with the musical activities of minorities and their impact on musical traditions in Europe. It also raises questions such as: How are musical traditions of minorities integrated in education and the public music life? Can music facilitate transcultural dialogue? And to what extent do musical practice and performance reassert the own cultural tradition in a foreign environment? Answers to those and similar questions as well as a review on what can be observed in the 21st century Europe are gathered in various thematic approaches. The book also provides model projects with a practical insight into the life and work with music of migrant and minority cultures across Europe